Controlling Exposure to Diesel Emissions in Underground Mines - Bugarski, Aleksandar D; Janisko, Samuel J; Cauda, Emanuele G; Noll, James D; Mischler, Steven E (Society for Mining, Metallurgy, and Exploration (SME), 2012)
This book was developed to assist the coal and metal/nonmetal underground mining industries in their efforts to reduce the exposure of workers to aerosols and gases from diesel-powered equipment. It includes information collected by researchers at the National Institute for Occupational Safety and Health/Office of Mine Safety and Health Research (NIOSH/OMSHR). Prior to the production of this text, the knowledge on this complex issue was fragmented. The goal of this volume is to make the information available in one easy-to-use reference. The book includes comprehensive, mine-specific programs for use by mechanics, mine ventilation engineers, industrial hygienists, mine managers, union health and safety representatives, and personnel responsible for the acquisition of diesel vehicles, engines, exhaust aftertreatment systems, fuels, and lubricants. The description of methods to reduce exposure to diesel aerosols includes curtailment of diesel particulate matter and gaseous emissions at their source, and controlling airborne pollutants with ventilation and personal protective equipment. This information should also help researchers in industry, government, and academia to identify areas that need to be addressed in future research and development efforts.